The Students’ Perception on the Use of Youtube Videos in English Language Teaching And Learning at Vocational High School - Lastaruli Manurung; Imelda Mallipa; Hengki Mofu (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
The use of YouTube videos in the English teaching process can help students in understanding the teaching materials. However, there are some factors that might affect the successful use of YouTube videos in classroom context. This research was conducted to investigate the students’ perceptions on the use of YouTube videos at SMK Kesehatan Terpadu Manokwari. Thirty-five students in class X Nursing were chosen as participants in this study. The questionnaire was administered to the students to collect the  data.  The  result showed  that  students  have  positive  perceptions  on  the use of YouTube videos in the English language teaching and learning process. The process of how the YouTube videos use in the classroom is explained.